Algernon charles swinburne;unofficial laureate. (MANCHESTER UNIV Press, 2017)
Algernon Charles Swinburne (18371909), dramatist, novelist and critic, was late Victorian England's unofficial Poet Laureate. Swinburne was admired by his contemporaries for his technical brilliance, his facility with classical and medieval forms, and his courage in expressing his sensual, erotic imagination. He was one of the most important Victorian poets, the founding figure for British aestheticism, and the dominant influence for fin-de-siècle and many modernist poets. Now available in paperback, this collection of eleven new essays by leading international scholars offers a thorough reval.